Ku koopetycji w sporcie. Wyzwania dla rynku o wysokiej konkurencji = Towards coopetition in sport. Challenges for the market of high competition. - Stosik, Aneta; Leśniewska, Aleksandra (Journal of Education, Health and Sport, 2016)
Stosik A., Leśniewska A., Ku koopetycji w sporcie. Wyzwania dla rynku o wysokiej konkurencji = Towards coopetition in sport. Challenges for the market of high competition. Journal of Education, Health and Sport. 2016;6(9):975-982. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.213149 https://pbn.nauka.gov.pl/sedno-webapp/works/769867 Original Text published © The Author (s) 2016. Stosik Aneta, Leśniewska Aleksandra. Wyzwania dla rynku o wysokiej konkurencji = Towards coopetition in sport. Challenges for the market of high competition. Quality in Sport. 2016;2(4):67-75. eISSN 2450-3118. DOI: http://dx.doi.org/10.5281/zenodo.212848, PBN: https://pbn.nauka.gov.pl/sedno-webapp/works/769845. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the1publication of this paper. Received: 6.11.2016. Revised 16.11.2016. Accepted: 24.11.2016. Streszczenie Główną determinantą działań organizacji usługowych stają się kreatywne poszukiwania przewag oraz niestandardowe rozwiązania systemowe. Poszukuje się nowych domen jakościowych oraz tworzy się nowe wartości dla klienta. Realizuje się procesy w oparciu o kluczowe kompetencje firm. Wszystkie działania mają prowadzić do zwiększenia efektywności organizacyjnej oraz skuteczności ekonomicznej, a nade wszystko tworzenia przewag w pozycji konkurencyjnej na rynku. Ostatnie lata rozwoju usług sportowych i rekreacyjnych wydają się niezwykle dynamiczne. Zmiana stylu życia i norm społecznych wymuszają na klientach poszukiwanie niestandardowych działań i indywidualizacji usług. Odpowiedzią na potrzeby klientów stają się specyficzne usługi trenerów personalnych, których działalność nie ogranicza się wyłącznie do kształtowania sylwetki klienta i jego kondycji fizycznej. Usługi te stają się coraz bardziej zindywidualizowane i oparte o komplementarność kompetencyjną. Wymogi klientów wymuszają zatem na trenerach personalnych poszukiwanie wsparcia i kooperowanie z innymi trenerami w branży w zakresie tworzenia specyficznych usług dla wysokich wymagań klienta indywidualnego. Tworzenie się przewagi konkurencyjnej poprzez współdziałanie z konkurentami stawia organizację w relacji jednoczesnego konkurowania i współdziałania, co określa się mianem koopetycji (Bengtsson, Kock 2000), stającej się normą na rynku usług rekreacyjnych. Dzieje się to szczególnie w obszarze usług trenerów personalnych. One of the most important aspects of leading service organizations is searching for advantages and creative solutions. Organizations look for new qualitative assets, create new values for their clients and create processes on the basis of their key competences. That kind of approach enable to improve organizational effectiveness and economic efficiency but more important to gain competitive advantages. Sport and recreational services develops extremely dynamically. Changes of lifestyle and social norms impose on clients non-standard actions and looking for individualized services. Personal training became a response for specific client’s needs. Personal trainers help not only to shape bodies and build fitness for clients, but also provide professional and individualized services by their competency complementarity. To achieve this personal trainers need to look for support and cooperation with other specialists and trainers in the whole customer service process. Building competitive advantages by cooperation with competitors cause a situation where personal trainers have to cooperate and compete with them at the same time - this phenomenon is called co-opetition and becomes more often a standard in recreational services.